Praktek Penentuan Arah Kiblat Bagi Panitia Pembangunan Masjid At-Tawwabin Mangkuyudan Rt 01/04 Ngabeyan Kartasura Sukoharjo - Harun Harun; Ruswa Darsono (Universitas Muhammadiyah Surakarta, 2010)
Member Of Mangkuyudan RT 01/04 mostly is majority religion islam havingstrong commitment to practice its(the religion teaching correctly as according tomanual al-Qur’an and al-Hadits. Constraint faced by them is Pertama, has not thereare a place to do religious service sholat fulfilling clauses fiqh, that is form of building mosque which its(the position towards direction of direction which tepatKedua, most of member of moslem mangkuyudan RT 01/04 still a few its(the knowledges about direction of direction according to calculation science falaq. Third, has not there is member of mangkuyudan RT 01/04 becoming place to enquire to religion problems, especially determination problem of direction of correct direction. Based on reasoning of this problem, hence some of member of sympathizer publics Muhammadiyah wishful to build mosque and formed [by] development committee of mosque’. As for becoming problems is development committee of mosque still be civil in the case of direction of correct direction and precise. They is there are strong desire to know about knowledge of direction of correct direction. Constraint faced by them is there is no institute or institution is its(the desire response. As according to problems is upper, hence solution done is perform [a] training of practice of determination of direction of direction with Resource person from the expert, in this case is Study Program Muamalat Islamic Religion faculty UMS. Determination Method of direction of direction applied in devotion of this public is apply object shadow because of sunshine. This model can be done by the way of determination with calculating difference Azimuth the sun and Kiblat of direction.Result practice of calculation determination of direction of direction in Mangkuyudan RT 01/04 Ngabeyan Kartasura Sukoharjo is Selisih Azimuth Kiblat ( Direction of Direction Counted - direction of Shadow) ) 294o 33’ 33,84